Correction: Correction: A Novel Rhabdovirus Associated with Acute Hemorrhagic Fever in Central Africa. - Gilda Grard; Joseph N Fair; Deanna Lee; Elizabeth Slikas; Imke Steffen; Jean-Jacques Muyembe; Taylor Sittler; Narayanan Veeraraghavan; J Graham Ruby; Chunlin Wang; Maria Makuwa; Prime Mulembakani; et al. (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1002924.].